Textured insoles affect the plantar pressure distribution while elite rowers perform on an indoor rowing machine - Vieira, Taian; Botter, Alberto; Gastaldi, Laura; Sacco, Isabel C. N.; Martelli, Francesco; Giacomozzi, Claudia (PLOS ONE, 2017)
Introduction During rowing, foot positioning on the foot stretcher is critical to optimise muscle force transmission and boat propulsion. Following the beneficial effects of textured insoles on gait and balance, this study aims at investigating whether passive stimulation of foot mechanoreceptors induced by these insoles may contribute to improving foot loading pattern and symmetry during indoor rowing. Methods Eleven elite rowers were assessed during controlled training on a standard rowing machine while wearing control, low-density or high-density textured insoles. Plantar pressure and knee and trunk kinematics were measured; performance data were recorded from the machine. Insole effect on kinematic parameters, peak and average values of foot force, contact area and position of centre of pressure was assessed with ANOVA and Bonferroni correction for pair-wise comparisons. Results A main effect was observed for force and contact area, with the high-density insoles providing greatest values (P<0.035). No interaction was observed between side and insole (P>0.190), even though symmetry was higher with high-density insoles. Kinematics (P = 0.800) and rowing performance were not affected by insole type; a consistent though not statistically significant increase in mean travelled distance was observed for denser insoles (P>0.21). Conclusion The high-density textured insoles affected foot loading distribution during indoor rowing. Rowers applied greater foot force and over a greater foot stretcher area with the high-density than the low-density and control insoles. These findings and the methodology applied may be relevant for the understanding and monitoring of rowing performance.